A 73‐year‐old man with loss of consciousness during treatment for miliary tuberculosis - Masahiro Ohgiya; Yuka Sasaki; Akira Yamane; Sumie Nakamura; Hirotoshi Matsui (Respirology Case Reports, 2022)
Key message Miliary tuberculosis is often associated with cerebral tuberculoma, which can manifest during treatment. We present images of a patient with cerebral tuberculoma detected due to emerging neurological symptoms during treatment of miliary tuberculosis.